Treatment Of Leachate By Scenedesmus Sp. Via Different Modestypes Of Bioreactors And Its Potential For Bioethanol Production - Abobaker, Mahmod Sidati Ali (2023)
In order to address human needs while safeguarding the environment, the utilization of sustainable material sources is imperative, this study focuses on the investigation of Scenedesmus sp. cultivation with varying concentrations of polysaccharide (starch), followed by its application in leachate treatment. The main objectives of this study were to determine the optimal concentration of polysaccharide for Scenedesmus sp. growth, evaluate its efficiency in treating municipal landfill leachate using batch, continuous, and membrane cultivation modes, and explore its capacity for bioethanol production. The methodology involved several stages, including the cultivation of Scenedesmus sp. with different concentrations of polysaccharide to identify the ideal growth condition. Subsequently, batch cultivation was conducted with varying pH levels, while continuous cultivation involved different dilutions. Membrane cultivation was carried out at various flow rates. The resulting algal biomass was then subjected to fermentation, with and without sonication, at different pH values to produce bioethanol. The results indicated that an optimal concentration of 0.8 g of polysaccharide yielded the highest growth of Scenedesmus sp. In batch cultivation, a pH of 7.0 exhibited the most effective removal percentages for COD, nitrogen, phosphorus, and carbohydrates. In continuous cultivation, the highest removal of COD, carbohydrate, phosphorus, and nitrogen occurred at a dilution rate of 0.220 h-1, accompanied by the highest specific rate of COD uptake.